Du plâtre et de la poésie. Les moulages d’après Michel-Ange à l’École des beaux-arts de Paris - Emmanuel Schwartz (In Situ)
In the 1840s, the minister Adolphe Thiers created a ‘shrine’ at the École des beaux-arts in Paris, made up of a collection of casts after Michelangelo. This collection showed the affinities between Michelangelo’s terribilità and the political and irreligious romanticism of Stendhal and Michelet. It had echoes in the poetry of Théophile Gautier and Baudelaire. For the sculptors Carpeaux and Rodin, Michelangelo’s works inspired audacious inventions. Taine used these Parisian plaster casts to show to his pupils the tragic symbolism of the original marbles.